2011
DOI: 10.1007/s00338-011-0744-4
|View full text |Cite
|
Sign up to set email alerts
|

CNP budgets of a coral-dominated fringing reef at La Réunion, France: coupling of oceanic phosphate and groundwater nitrate

Abstract: Productivity, nutrient input, nutrient uptake, and release rates were determined for a coral-dominated reef flat at La Réunion, France, to assess the influence of groundwater nitrogen on carbon and nutrient budgets. Water samples were collected offshore in the ocean, at the reef crest and back reef for nutrients, picoplankton, pH, and total alkalinity. Volume transport of ocean water across the reef flat was measured using both current meters and drogues. Groundwater advected onto the reef flat and mixed with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
39
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(47 citation statements)
references
References 20 publications
8
39
0
Order By: Relevance
“…km). The factors forcing nutrient fluxes over coral reefs are, thus, unlikely to be as constant in space and time as generally assumed (as noted by Atkinson et al 2001;Steven and Atkinson 2003;Cuet et al 2011a). Oceanographic processes control reef-scale delivery of dissolved nutrients by driving fluctuations in incoming nutrient concentrations over daily to seasonal time scales.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…km). The factors forcing nutrient fluxes over coral reefs are, thus, unlikely to be as constant in space and time as generally assumed (as noted by Atkinson et al 2001;Steven and Atkinson 2003;Cuet et al 2011a). Oceanographic processes control reef-scale delivery of dissolved nutrients by driving fluctuations in incoming nutrient concentrations over daily to seasonal time scales.…”
Section: Discussionmentioning
confidence: 97%
“…Comparatively few studies have quantified fluxes within natural reefs systems at the community scale (Crossland and Barnes 1983;Baird et al 2004;Cuet et al 2011a), largely due to the fact that uptake rates are often too slow to detect over smaller spatial scales (Atkinson and Smith 1987;Atkinson and Bilger 1992 Atkinson and Falter 2003). Although gross flux estimates have rarely been reported for natural systems Falter et al 2004;Cuet et al 2011a), the present estimates (Tables 4 and 5 Estimates of POM fluxes are even more limited than for dissolved inorganic nutrients (but see Genin et al 2009;Wyatt et al 2010;Cuet et al 2011a). Thus, although the likely significance of POM in community-and reef-scale nutrient budgets has been widely recognized for many years (Odum and Odum 1955;Ayukai 1995;Yahel et al 1998), its quantitative importance is still poorly understood.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In relatively oligotrophic coastal systems with coral reefs, such groundwater-associated nutrient fluxes may sustain the reef community production (Cuet et al, 2011), result in increases in diversity and occurrence of algae and sponge where relatively low salinity is present (Houk and Starmer, 2010), or induce the proliferation of diatom and cyanobac-teria (Blanco et al, 2011). In addition, groundwater tidally driven into nearshore ecosystems was found to be negatively correlated with seagrass habitat conditions (Houk et al, 2013).…”
Section: Seasonal and Regional Extrapolationsmentioning
confidence: 99%
“…Such groundwater characterized by a high N : P ratio thus could have significant impacts on coastal reef ecosystems, consid-ering that benthic marine plants are much more depleted in P, with an N : P ratio of about 30 : 1 (Atkinson and Smith, 1983). Cuet et al (2011) have found that the net community production in a coral-dominated fringing reef at La Réu-nion, France, is sustained by net uptake of new nitrogen from groundwater and net uptake of phosphate from the ocean.…”
Section: Introductionmentioning
confidence: 99%